2016
DOI: 10.1007/s40858-016-0088-2
|View full text |Cite
|
Sign up to set email alerts
|

Histological characterization of resistance to Meloidogyne incognita in Avena sativa

Abstract: Root-knot nematodes, especially Meloidogyne incognita, are recognized by expressive damages on important agronomic crops worldwide. White oat (Avena sativa) is an excellent alternative to sustainable management of nematodes especially when used in crop rotation with another plant species. In this context, the aim of the present work was to study the resistance of IPR Afrodite oat cultivar to M. incognita, using histopathological methods in a comparative approach with the susceptible cultivar URSFAPA Slava. Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 21 publications
(23 reference statements)
2
8
0
Order By: Relevance
“…The higher degree of resistance of 'IPR Afrodite' to both species of nematodes agrees to the results of research already done with this cultivar by other authors (Marini et al, 2016;Riede et al, 2015). Marini et al (2016) found a reduction in the penetration of juvenile nematodes in the roots of this oat genotype, with lignified cells and intracellular spaces filled with phenols, which is an indicative of the plant defense response to nematode attack. This suggests that the chemical profile of oat genotypes is one of the determinant Table 1.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The higher degree of resistance of 'IPR Afrodite' to both species of nematodes agrees to the results of research already done with this cultivar by other authors (Marini et al, 2016;Riede et al, 2015). Marini et al (2016) found a reduction in the penetration of juvenile nematodes in the roots of this oat genotype, with lignified cells and intracellular spaces filled with phenols, which is an indicative of the plant defense response to nematode attack. This suggests that the chemical profile of oat genotypes is one of the determinant Table 1.…”
Section: Discussionsupporting
confidence: 91%
“…The values of the relative density of nematodes in the root system confirms the characterization of genotypes based on the RF as they show congruence between them (Shigueoka et al, 2016). The higher degree of resistance of 'IPR Afrodite' to both species of nematodes agrees to the results of research already done with this cultivar by other authors (Marini et al, 2016;Riede et al, 2015). Marini et al (2016) found a reduction in the penetration of juvenile nematodes in the roots of this oat genotype, with lignified cells and intracellular spaces filled with phenols, which is an indicative of the plant defense response to nematode attack.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…HR represents one of the main plant defense mechanisms, causing histological changes after nematode penetration in coffee roots, with cell death near the J2 infection point (Silva et al, 2013). HR reactions are frequently accompanied by cell death surrounding nematode penetration, during its migration or after the establishment of the giant cell (Rodrigues et al, 2000;Marini et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Plant resistance mechanisms to nematode infection involve pre-or post-infectional reactions (Huang, 1985;Marini et al, 2016). One of the mechanisms involved is the hypersensitive reaction (HR), which induces histological changes after nematode penetration in root tissues, such as the death of the cells close to the giant cell induced by the nematode (Anthony et al, 2005;Albuquerque et al, 2010;Silva et al, 2013;Marini et al, 2016). Several works have been published describing the relationships between coffee and root-knot nematodes, particularly to M. incognita (Albuquerque et al, 2010) and M. exigua (Rodrigues et al, 2000;Anthony et al, 2005).…”
Section: Introductionmentioning
confidence: 99%